Agrimonia eupatoria subsp. major stat. nov. (Rosaceae) and notes on the Agrimonia eupatoria aggregate - Iamonico, Duilio (Phytotaxa, 2017)
The name Agrimonia eupatoria subsp. major stat. nov. (Rosaceae) is proposed. A lectoptype and isolectotype are proposed for the Boissier’s basionym on the basis of the examination of type materials and other specimens. For the nomenclatural purposes the names A. graeca (nom. inval. according to the Art. 36.1c of the ICN), A. eupatoria sensu stricto (lectotype at LINN), A. eupatoria subsp. grandis (neotype at FI, designated in this paper), “A. eupatoria var. grandis” by Vollmann (isonym, Art. 6.3 Notes2 of the ICN) and “A. grandis” by Dobroczajeva (isonym, Art. 6.3 Notes2 of the ICN) are also discussed. A morphological comparison among the taxa included in the Agrimonia eupatoria aggregate, as well as a diagnostic key, are also given.